A Complex Endomembrane System in the Archaeon Ignicoccus hospitalis Tapped by Nanoarchaeum equitans - Heimerl, Thomas; Flechsler, Jennifer; Pickl, Carolin; Heinz, Veronika; Salecker, Benjamin; Zweck, Josef; Wanner, Gerhard; Geimer, Stefan; Samson, Rachel Y.; Bell, Stephen D.; Huber, Harald; Wirth, Reinhard; et al. (Frontiers in Microbiology, 2017)
Based on serial sectioning, focused ion beam scanning electron microscopy (FIB/SEM), and electron tomography, we depict in detail the highly unusual anatomy of the marine hyperthermophilic crenarchaeon, Ignicoccus hospitalis. Our data support a complex and dynamic endomembrane system consisting of cytoplasmic protrusions, and with secretory function. Moreover, we reveal that the cytoplasm of the putative archaeal ectoparasite Nanoarchaeum equitans can get in direct contact with this endomembrane system, complementing and explaining recent proteomic, transcriptomic and metabolomic data on this inter-archaeal relationship. In addition, we identified a matrix of filamentous structures and/or tethers in the voluminous inter-membrane compartment (IMC) of I. hospitalis, which might be responsible for membrane dynamics. Overall, this unusual cellular compartmentalization, ultrastructure and dynamics in an archaeon that belongs to the recently proposed TACK superphylum prompts speculation that the eukaryotic endomembrane system might originate from Archaea.